2009
DOI: 10.1126/science.1168594
|View full text |Cite
|
Sign up to set email alerts
|

The Earliest Horse Harnessing and Milking

Abstract: Horse domestication revolutionized transport, communications, and warfare in prehistory, yet the identification of early domestication processes has been problematic. Here, we present three independent lines of evidence demonstrating domestication in the Eneolithic Botai Culture of Kazakhstan, dating to about 3500 B.C.E. Metrical analysis of horse metacarpals shows that Botai horses resemble Bronze Age domestic horses rather than Paleolithic wild horses from the same region. Pathological characteristics indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
378
1
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 567 publications
(429 citation statements)
references
References 9 publications
9
378
1
14
Order By: Relevance
“…Given that organic residue preservation in these regions is excellent, the lack of beeswax would seem to establish the ecological limit of A. mellifera at that time. Similar arguments are likely to account for the absence of beeswax residues from >350 prehistoric pottery vessels from the Eurasian Steppe 28 .…”
mentioning
confidence: 78%
“…Given that organic residue preservation in these regions is excellent, the lack of beeswax would seem to establish the ecological limit of A. mellifera at that time. Similar arguments are likely to account for the absence of beeswax residues from >350 prehistoric pottery vessels from the Eurasian Steppe 28 .…”
mentioning
confidence: 78%
“…However, as more archaeological residues and modern reference fats are analysed, it is becoming clear that this may not be a universal solution to the question of identifying fats. Analysis of modern, reference horse fats from Kazakhstan showed almost complete overlap in carbon isotopic values between dairy and adipose fats (32,69). Measurements of C 3 plant oil isotopic signatures show them to lie either on the mixing line between ruminant and non-ruminant adipose fats (70) or in the same range as cattle adipose fats (68).…”
Section: Identification Of Fatty Materialsmentioning
confidence: 99%
“…Likewise, aquatic products (Patrick et al 1985;Hansel et al 2004;Craig et al 2007;Hansel and Evershed 2009;Shoda et al 2017), plant oils and waxes denoting vegetable and plant oil consumption/ processing (Evershed et al 1991;Copley et al 2001a;Copley et al 2001b;Reber et al 2004;Copley et al 2005;Cramp et al 2011;Dunne et al 2016) and beeswax (Heron et al 1994;Charters et al 1995;Evershed et al 1997b;Regert et al 2001;Evershed et al 2003;Roffet-Salque et al 2015), resins, tars and bitumen (Beck et al 1989;Mills and White 1989;Evershed et al 1997a;van Bergen et al 1997;Urem-Kotsou et al 2002;Stern et al 2003;Buckley et al 2004;Stern et al 2008;Connan et al 2013;Brown et al 2014: Brettell et al 2014 have been identified in connection with a wide range of technological and cultural activities. On a broader scale, lipid residue analyses can provide insight into the domestication of plants and animals, the development of animal husbandry practices and ecological and environmental changes through time (Evershed 2008b;Evershed et al 2008;Outram et al 2009;Dunne et al 2012;Dunne et al 2016;Roffet-Salque et al 2017).…”
Section: Introductionmentioning
confidence: 99%